2022
DOI: 10.1007/s00296-022-05125-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ECG testing and characteristics among new hydroxychloroquine and chloroquine users within a multi-center tertiary care center

Abstract: COVID-19 raised concern regarding cardiotoxicity and QTc prolongation of hydroxychloroquine (HCQ) and chloroquine (CQ). We examined the frequency and patient factors associated with ECG testing and the detection of prolonged QTc among new HCQ/CQ users in a large academic medical system. 10,248 subjects with a first HCQ/CQ prescription (1/2015–3/2020) were included. We assessed baseline (1 year prior to and including day of initiation of HCQ/CQ through 2 months after initial HCQ/CQ prescription) and follow-up (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The most common study designs were retrospective cohort (n = 19), prospective cohort (n = 6), case-controlled (n = 6), and retrospective observational (including pharmacovigilance; n = 3) (Table 1). 5, Of the 34 studies included, only 11 provided mean QTc and OR for prolonged QTc for metaanalysis (Table 2). Six studies provided the mean QTc difference, and all reported outcomes in HCQ users alone.…”
Section: Publications Includedmentioning
confidence: 99%
See 4 more Smart Citations
“…The most common study designs were retrospective cohort (n = 19), prospective cohort (n = 6), case-controlled (n = 6), and retrospective observational (including pharmacovigilance; n = 3) (Table 1). 5, Of the 34 studies included, only 11 provided mean QTc and OR for prolonged QTc for metaanalysis (Table 2). Six studies provided the mean QTc difference, and all reported outcomes in HCQ users alone.…”
Section: Publications Includedmentioning
confidence: 99%
“…Eighteen studies reported outcomes in populations that pooled rheumatic diseases in the analysis, most commonly RA and SLE. 5, Other diseases reported included unspecified mixed rheumatic disease, systemic sclerosis, undifferentiated connective tissue disease, mixed connective tissue disease, Henoch-Schönlein purpura, urticarial vasculitis, proteinase 3 (PR3) vasculitis, myeloperoxidase (MPO) vasculitis, eosinophilic granulomatosis with polyangiitis, Takayasu arteritis, Behçet's disease, adult-onset Still's disease, polyarteritis nodosa, relapsing polychondritis, calcium pyrophosphate disease, unspecified inflammatory arthritis, Sjögren disease, sarcoidosis, spondyloarthropathy, polymyalgia rheumatica, juvenile idiopathic arthritis, morphea, osteoarthritis, and cutaneous lupus erythematosus. Disease duration and duration of HCQ/CQ therapy were infrequently and inconsistently reported and thus could not be extracted.…”
Section: Patient and Control Populationsmentioning
confidence: 99%
See 3 more Smart Citations